Reclaiming Faith and Justice: A Narrative Review of Islamic Feminism - Lestari, Putri Ayu (Sinergi International Journal of Islamic Studies, 2024)
This study presents a narrative review on Islamic feminism, examining how gender justice is conceptualized and practiced in Muslim-majority societies and diaspora communities. The review aims to identify key themes, challenges, and transformative strategies that define the Islamic feminist discourse. Methodologically, the study employed a systematic literature search across databases including Scopus, Google Scholar, and JSTOR, using targeted keywords and inclusion criteria to identify peer-reviewed articles relevant to feminist hermeneutics, activism, legal reform, and gender dynamics in Islam. The analysis revealed five central themes: feminist reinterpretation of religious texts, women's socio-political activism, intersections between national identity and feminism, cultural-religious negotiations, and internal tensions within Islamic feminist movements. Empirical data from various contexts demonstrated that systemic barriers—including patriarchal state structures, conservative religious narratives, cultural norms, and legal discrimination—significantly hinder the progress of gender equality. Comparative findings across Malaysia, Indonesia, Iran, and South Africa highlighted the contextual specificity and universality of these challenges. The discussion underscored the need for legal reform, inclusive education, and community-based advocacy to dismantle patriarchal systems. It also emphasized gaps in the literature, including limited attention to LGBTQ+ voices, digital activism, and ecofeminism. The study concludes that Islamic feminism requires an integrated strategy rooted in education, cultural engagement, and inclusive theology to create equitable societies.